Regulatory issues associated with graywater reuse - Glenn, Robert Triumph, author; Sharvelle, Sybil, advisor; Roesner, Larry, committee member; Glick, Scott, committee member (Colorado State University. Libraries, 2012)
Concerns over limited water resources in arid and semi-arid regions in addition to overloaded and/or costly wastewater treatment facilities have resulted in utilities looking toward new concepts for water management. This is particularly true in the Southwestern United States. One approach which is increasingly gaining popularity is the reuse of graywater for nonpotable applications. Graywater reuse has been known to be prevalent in the U.S. for at least 10 years. A study conducted by the Water Conservation Alliance of Southern Arizona showed that 13% of homes were reusing graywater in the year 2000. Despite the prevalence of graywater reuse, most current regulations have not been based on science and states currently looking toward developing regulations and guidelines on the safe reuse of graywater are seeking guidance on doing so. Also, the link between graywater constituents and risk to human health has not been well studied. Therefore, the risks posed to human health by graywater reuse remain largely unknown. The objective of this project is to gather useful data on the water quality, currently available technologies and standards for integrating graywater systems into various types of localized sites. Additionally, surveys from state health officials (including states that allow graywater use and states that lack a graywater regulation) provide insight on the key issues associated with implementing graywater regulations. The data gathered will help regulatory agencies make decisions based on water quality information, available technologies and standards. A spreadsheet based end product was created to manage the vast amount of information and sort all the data on water quality, regulations and treatment technologies.
Keywords: water reuse; graywater; urban water management; regulations